Avaliação integrada da paisagem na área do Parque Nacional da Chapada dos Veadeiros (Goiás) - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
The Chapada dos Veadeiros National Park (PNCV) is considered by Unesco (United Nations Educational, Scientific, and Cultural Organization) a Natural World Heritage Site and the core area of the Savanna Biosphere Reserve. It is one of Brazil's Hotspots, with its phytophysiognomies entirely within the Savanna domain. Established in 1961, by President Juscelino Kubitschek, under the name Parque Nacional do Tocantins, it had an area of approximately 625 thousand hectares, which was successively reduced. On May 11, 1972, the park was given its boundaries of 171,924 hectares, based on diagnoses made by a commission of the Ministry of Agriculture. Nine years later, in 1981, the PNCV lost part of its territory, being restricted to 65 thousand hectares, because of the "Alto Paraíso Agricultural Project", presented by the Government of Goiás, requesting, at the time, the passage of the GO-239 highway between Morro da Baleia and Morro do Bração. In 2001, it was recognized as a Natural Heritage Site of Humanity by UNESCO, having its area increased to 235,000 hectares. However, the expansion decree was suspended in 2003 by the Federal Supreme Court, due to flaws in the public consultation process, returning to the area defined in 1981. With a new decree of June 17, 2017, it had its area expanded to 240,586.56 hectares (PM,2019). The Pouso Alto Environmental Protection (APA) Area was created by Decree No. 5.419, of May 7, 2001, it is a Pouso Alto Environmental Protection Area, intended to foster sustainable development and preserve the flora, fauna, springs, geology and landscaping of the Pouso Alto region, located, in the Chapada dos Veadeiros National Park, in this State (GOIÁS, 2001).The overall objective of this dissertation is to understand how the process of land use and land cover, environmental fragility and vulnerability occurred in the area of the PNCV: since the process of creation (1961); the area reductions (1972 and 1981); and the process of expansion, (2001 and 2017). This work is integrated in the PNCV area, with mapping for analysis of landscape geoecology, vulnerability and environmental fragility. The modeling results indicated that, in relation to the potential fragility, what predominates is the Medium class with 61.50%, with the area of approximately 147.992,22 hectares, and the Emergent fragility with the Low class, with 85.1% with an area of 204.616,97 hectares. In relation to environmental vulnerability, what predominates is the medium class with an area of 198.902,07, with a percentage of 82.56%. Despite the geomorphology and soil types of the region presenting high fragility or vulnerability, the conditions of preservation of the Savanna in the region, reflects in the stability of the landscapes.
Integrated iandscape assessment in the area Chapada dos Veadeiros National Park (Goiás)
Keywords: Cerrado; Geoecologia da paisagem; Vulnerabilidade ambiental; Fragilidade ambiental; Savanna; Landscape geoecology; Environmental vulnerability; Environmental fragility; CIENCIAS HUMANAS::GEOGRAFIA